KNOWLEDGE AWARENESS AND BEHAVIOUR OF NON-MEDICAL STUDENTS ABOUT CARDIOVASCULAR DISEASES - Mustaqeem, Marium; Sadullah, Samiyah; Farooq, Muhammad Zain; Waqar, Wajiha; Fraz, Tayyab Raza (Journal of Ayub Medical College Abbottabad, 2015)
Background: Cardiovascular diseases is the leading cause of death worldwide, yet very little data is available assessing the awareness of the younger population of Pakistan. The purpose of this study was to evaluate the awareness, knowledge and the preventive measures taken to avoid the health issues related to cardiovascular diseases. Methods: It was a community based cross sectional descriptive study to assess the awareness and behavior in young non medical students. A questionnaire was developed and survey was conducted on 300 non medical students enrolled in different universities of Pakistan. Data analysis was performed using SPSS-16. Results: The sample consisted of 300 students aged between 16 and 32 years.6.7% of the participants had history of blood pressure, 0.7% had diabetes, and 68.3% had a family history of cardiovascular diseases. 17.4% students were smokers. In the knowledge section, only 22% respondent scored above 20 out of 28 showing lack of knowledge. 42.7% participants were concerned about developing coronary artery diseases. 43.3% and 6.7% knew their blood pressure and cholesterol level respectively.33.3% and 41.7% regulate their dietary fat and salt intake respectively. Conclusion: Our study elucidates that cardiovascular diseases are not perceived as major risk by Non Medical Students. Lack of knowledge, physical inactivity, and high positive family history render the target population prone to cardiovascular diseases. The findings of study indicates the need for heart disease awareness campaigns for young population, to escalate the preventive actions and adoption of healthy lifestyles so as to lower the incidence of cardiovascular diseases in Pakistan.